Demystifying the Medical Literature. Issue 4 (December 2016) - Greeley, Christopher
The published literature is not just the ongoing record of current medical and scientific knowledge; it is a record of the past and can give an eye toward future knowledge. Reading the published literature can give a view of the evolution of knowledge on a particular question, the growth of a discipline, the identification of new diseases, and the refinement of diagnostic tests. The reality is that most busy physicians read only the abstract of an article. The purpose of this article is to place published medical literature into a context and to provide some considerations for critically evaluating articles. This paper will provide historic background of evidence-based medicine and medical publications. Specific strategies for critical literature appraisal are highlights and pitfalls to avoid are outlined.